An optimization of process parameters for deep desulfurization of model fuel by ZSM-5/ZnO photocatalyst using response surface method. (2nd October 2017) - Sahragard, Hojjat; Khosravi-Nikou, Mohammad Reza; Maddahi, Mohammad Hossein
ABSTRACT: One of the major factors that causes air pollution are sulfur oxides) SOx ) that exiting from vehicles exhaust by combustion of fossil fuel. Although hydrodesulfurization method has always been the option in oil refineries to reduce sulfur contents, but it is almost impossible to meet stringent new environmental regulation by this method. The Achilles heel of the conventional method is weakness in removing aromatic sulfur recalcitrant compounds. In the present research, photocatalytic oxidative desulfurization (PhOD) based on the ZSM-5/ZnO catalyst is developed. n-Decane as the model fuel and benzothiophene (BT) and dibenzothiophene (DBT) as the sulfur compounds are used. Then by the response surface method the optimum conditions were developed. The result indicates that catalyst with 6%wt Zn/ZnO, 45 min reaction time, UV power of 32 watts and catalyst to fuel ratio of 2 gr/L is able to remove BT and DBT with efficiency of 86.1% and 74.0%, respectively.